Unwelcome Guests? The Effects of Refugees on the Educational Outcomes of Incumbent Students - Figlio, David; Özek, Umut (Journal of Labor Economics, 2019)
A point of contention in the refugee crisis involves possible adverse effects on host communities associated with poor, low-skilled migrants with low host-community language knowledge. We use unique matched birth and schooling records to examine the effects of a large influx of poor, non-English-speaking Haitian migrants into Florida public schools immediately following the devastating 2010 earthquake. We find zero or modestly positive estimated effects of these migrants on the educational outcomes of incumbent students in the year of the earthquake or in the 2 years that follow, regardless of the socioeconomic status, grade level, ethnicity, or birthplace of incumbent students.